RELASI SOSIAL DALAM PENGELOLAAN LAHAN REHABILITASI TAMAN NASIONAL MERU BETIRI (Studi Kasus Desa Wonoasri Kecamatan Tempurejo Kabupaten Jember) - Zulfidda Lillah; Diah Puspaningrum (University of Jember, 2020)
Forest rehabilitation in Meru Betiri National Park is the main point in environmental sustainability. Forest land rehabilitation activities include breeding ecosystems for security in the forest. The method of determining the research area is done intentionally (purposive method) and the research method uses a qualitative approach. Determination of informants is done by snowball sampling method. The data collection method was carried out by observation, interview and document study and analyzed using the Miles and Huberman analysis method. The results showed that social relations that occur in the management of rehabilitation have 2 forms of domains, namely 1) interpersonal domains that can be seen with communal relations, collegial relations and hirearkis relations. Judging from its power relations are divided into symmetrical and asymmetrical relationships. Symmetrical relationship occurs between rehab land farmers where rehab land farmers have an equal position can be seen from daily relationships and friendly relations in managing rehabilitation land. Asymmetrical relationship that occurs in the rehabilitation of land management occurs between the TNMB and farmers of the rehabilitation land where the TNMB party has the highest authority in the management of rehabilitation land. Keywords : Social Relation, Rehabilitation land, Meru Betiri National Park